Facilitating access to justice: Exploring the experiences of autistic individuals arrested and detained in police custody - Holloway, Chloe (2019)
This thesis explores the lived experiences of autistic individuals who have been arrested and detained in police custody as suspects of a criminal offence. It examines the difficulties that autistic individuals encounter in this setting and the support they may receive to manage these difficulties. In particular, it considers whether the safeguards outlined by the Police and Criminal Evidence Act 1984 and Code of Practice C effectively support autistic individuals throughout the custody process.